A 14 - years mapping of research productivity of the School of Business academicians at Mzumbe University, Tanzania: A bibliometrics analysis - Shemahonge, Adam. H.; Mosha, Goodluck E.; Siyao, Peter, O. (Dar es Salaam University Press (DUP), 2024)
The purpose of this study is to determine the research productivity of the School of Business (SoB) academic staff at Mzumbe University between 2007 and 2020. The study employed a mixed approach to data collection. A total of 58 SoB academic staff were used in this study. Quantitative data were extracted from google scholar using the Publish or Perish (PoP) software. Qualitative data were collected using an interview guide. The quantitative data were analysed using a Microsoft Excel Spread sheet whereas qualitative data were analysed using content analysis. The findings indicate that a total of 253 publications were recorded for all 14 years yielding a low yearly average of 18.07 publications for all academicians and an average of only 4.4 publications for each SoB academician. Individual productivity analysis shows Dr. Hawa Tundui as the top-ranking academician with 20 publications. The distribution of citations for SoB academicians has Dr. Ernest Mwasalwiba ranking first with 924 citations. The authorship pattern at SoB was dominated by single-authored publications 100 (40%) followed by two-authored publications 87 (34%) with an average of 0.49 degree of collaboration. The subject-wise distribution reveals that SoB academic staff are more interested in writing on Small and Medium Enterprises (SMEs) and business area. With regard to the journal of preference, most of the SoB scholars prefer to publish in the Uongozi Journal of Management and Development Dynamics (UJMDD). This bibliometrics analysis was limited to SoB. Other studies should cover all MU schools, faculties, directorates and other campuses. To improve the growth of research and publications at MU, collaborations in research and publications; formulating a friendly and favourable research policy; awareness creation about online research platforms such as registering on Google Scholar among MU academicians, Research Gate and ORCID among others and capacity building in publishing skills are highly recommended. This is the first time a bibliometrics analysis has been conducted to determine research productivity at MU and which covered a field of business in Tanzania